2015
DOI: 10.1016/j.orggeochem.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriohopanepolyols in tropical soils and sediments from the Congo River catchment area

Abstract: a b s t r a c tThe Congo River basin drains the second largest area of tropical rainforest in the world, including a large proportion of pristine wetlands. We present the bacteriohopanepolyol (BHP) inventory of a suite of tropical soils and, from comparison with published data, propose some initial ideas on BHP distribution controls. Strong taxonomic controls on BHP production are evident in wetland sediments. Dominant within the suite were 35-aminobacteriohopane-31,32,33,34-tetrol (aminotetrol) and 35-aminoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…The aminopentol isomer (I'; Fig. 1C) detected at 408C has been described previously (van Winden et al, 2012) and found in environmental settings where aminopentol is abundant relative to other BHPs Wagner et al, 2014;Spencer-Jones et al, 2015). Additionally at 408C, which was dominated by a Methylobacter sp.…”
Section: Resultssupporting
confidence: 79%
“…The aminopentol isomer (I'; Fig. 1C) detected at 408C has been described previously (van Winden et al, 2012) and found in environmental settings where aminopentol is abundant relative to other BHPs Wagner et al, 2014;Spencer-Jones et al, 2015). Additionally at 408C, which was dominated by a Methylobacter sp.…”
Section: Resultssupporting
confidence: 79%
“…The near-absence of soil-marker BHPs in AMV (Table 2) may still point towards in-situ marine production of aminopentol. However, the relative abundance of soil-markers in terrestrial settings has recently been found to be strongly influenced by environmental factors; higher temperatures and low pH (in peatlands) can both strongly reduce the relative proportion of soil marker BHPs as a proportion of total BHPs [40,110,111]. Aminopentol was found in NZS sediments that also contained soil marker BHPs (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, only limited depletion in 13 C, with values between -25‰ and -40‰, have been reported for hopanoids with an inferred methanotrophic origin from modern peat bogs [37,38] as well as other ancient lignite deposits [39]. Also, BHPs in Congo deep sea fan sediments, originating from low-latitude wetlands [40], had higher 13 C values than expected (i.e., C 30 hopanol ~ -41‰; [14]). In marine CH 4 seep carbonates from the Gulf of Mexico, BHPs, hopanoic acids, and 4-methylated sterols of aerobic methanotrophs were found with similar δ 13 C values as the CH 4 source [41].…”
Section: Introductionmentioning
confidence: 99%
“…Congolaise soils is indirectly supported by the high concentrations and 13 C composition of aminobacteriohopanepolyls in soils of this region (Talbot et al, 2014;Spencer-Jones et al, 2015). Therefore, in addition to higher CBT values, increased incorporation of GDGTs from swamp-forest soils during high discharge should lead to elevated GDGT-0/cren ratios, as is observed (Figure 5.4D).…”
Section: Significant Methanogenesis In Cuvettementioning
confidence: 57%